Use of quality measurement across US dental delivery systems: a qualitative analysis. (1st September 2015) - Alrqiq, Hosam M.; Edelstein, Burton L.
Abstract: Objectives: Dentistry is increasingly challenged by payers and the public to demonstrate quality measurement (QM) activities that substantiate value. Unknown is how various components of the US oral health‐care financing and delivery systems have adopted QM. The objective of this study is to explore QM activities by US dental delivery, management, financing, and related organizations. Methods: Using a structured interview guide based on a novel conceptual framework that incorporates factors influencing QM intention, adoption, and implementation, 19 key informant interviews were conducted. Informants represented safety net delivery programs (health center, nonprofit mobile, hospital‐based, Veterans Administration, and tribal dental programs), private delivery organizations (private practice, closed panel HMO, and for‐profit mobile dental programs), training programs that deliver care (dental and dental therapy programs), management organizations (private and Medicaid group practice management companies), care financing organizations (Medicaid managed care plan, state Medicaid program, dental benefits companies), and dental quality organizations (institute and dental professional organization). Interviews were transcribed and analyzed qualitatively. Results: Informants report wide variation in the intensity of QM efforts with organizational leadership cited as most influential. Motivation to adopt QM efforts is more often internal than imposed. Data management and information technology both facilitate and limit QM activities. QM activities are associated with operational improvements including use of guidelines and refinements of mission. Organizational type and size appear to influence QM programs. Conclusion: The current status of QM is highly variable across dental organizations because organizational leadership, needs, and requirements vary according to mission and structure.